Electrokinetic driven flow with magnetic properties of viscoelastic fluid with thermal analysis and chemical mechanism in a rotational microfluidic system - S. Ravikumar; S. Farooq; Hamdy Khamees Thabet; Fadhil Faez Sead (Case Studies in Thermal Engineering, 2025)
This research explores the interaction of electrokinetic and magnetohydrodynamic forces on the peristaltic activity of a viscoelastic Jeffery fluid within a rotating microfluidic system, incorporating thermal and chemical effects. The peristaltic wave strategy provides a basis for the present model, which features nonuniform boundaries formed by differing amplitudes and phases. The governing equations can be solved analytically by employing low Reynolds number and long wavelength approximations. The Debye-Hückel linearization is used to further simplify the Poisson-Boltzmann equations. Notice that an elevation in the jeffery fluid parameter diminishes fluid velocity owing to augmented elastic resistance and extended relaxation durations. Electroosmosis and helmholtz-smoluchowski velocity augment fluid velocity, but hall current and darcy number diminish it due to interactions with magnetic and electrokinetic forces. The skin friction coefficient rises with the helmholtz-smoluchowski velocity and electroosmosis parameter, signifying increased resistance next to the walls. Furthermore, the pressure gradient diminishes with rising darcy and electroosmosis parameters, hence enhancing flow efficiency, while the hall current and hartmann number augment it owing to intensified magnetic and electrokinetic effects. The prandtl number and joule heating significantly elevate fluid temperature by enhancing thermal energy retention, whereas thermal radiation and biot numbers promote heat dissipation, leading to a reduction in temperature. The research is motivated by the need to understand the interrelated electrokinetic and magnetohydrodynamic phenomena in viscoelastic fluids, which is essential for the development of biomedical microdevices and the optimization of complex transport in MEMS technologies. This paper presents design solutions for high-efficiency microfluidic and lab-on-chip systems, delivering analytical insights into the effects of electro-magneto-thermal-fluidic interactions on flow, temperature, and mass transfer in rotating microchannels.